Avaliação da clorexidina no controle do biofilme dental em crianças portadoras de necessidades especiais - Chibinski, Ana Cláudia Rodrigues (2004)
Disabled children show difficulties to perform the mechanical control of dental plaque and show a high prevalence of periodontal disease. In this group of patients, the association between chemical agents and dental brushing runs into an exact indication of use and chlorhexidine is the best suited agent for this purpose. Therefore, this research main objective was to evaluate two chlorhexidine vehicles for plaque control in disabled children, as well as parents’ opinions about the home usage protocols tested. The sample consisted of 29 patients, with medical diagnosis of mental deficiency aging between seven and twelve years old. The protocols tested used chlorhexidine digluconate 0,12%, delivered as a gel (GCH protocol) and as a spray (SCH protocol). A placebo gel (GP protocol) and a placebo solution (SP protocol) were used as control. The tested agents were administered twice a day by the handicapped patient’s parents, who also brushed the children’s teeth with a placebo dentifrice. The study was designed as a double-blind, crossover research, with four experimental periods (ten days) apart from each other by three washout periods (fifteen days). The patients were evaluated at the beginning and at the end of each experimental period by one calibrated examiner, using the Quigley and Hein plaque index and the presence or abscence of gingival bleeding during probing. Similar clinical conditions were observed at the beginning of all tested protocols when the plaque index (p=0,133) and the gingival bleeding index (p=0,060) were considered. After GCH and SCH protocols, there was a significant reduction in plaque and gingival indices (p<0,0001). There were seen statistically significant differences when comparing post treatment indices from GCH protocol with GP and SP protocols or from SCH protocol with GP and SP protocols. When the four protocols were completed, the parents answered a questionaire. They reported a greater level of difficulty when applying gel in opposition to spray (p=0,007), which was their preferable vehicle for daily use (p=0,035). It is concluded that plaque indices and the presence of gingival bleeding were reduced by chlorhexidine treatment, regardless the employed vehicle; chlorhexidine delivered as a gel offered greater application difficulties and spray was the parent’s choice for daily use of this chemical agent.